Factors influencing post-partum women’s choice of an implantable contraceptive device in a rural district hospital in South Africa - Francois Potgieter; Paul Kapp; Francois Coetzee (South African Family Practice)
Background: A single-rod subdermal contraceptive implant containing 68 mg of etonogestrel, ImplanonNXT®, was introduced to the South African healthcare system in 2014. Initially the new device was well received but later uptake tapered off. A need was identified to determine the factors that influence women’s choices with regard to the use of ImplanonNXT® in order to improve its uptake. The aim of this study was to explore the factors that influence women’s choice of ImplanonNXT®. Method: A qualitative study was performed, using semi-structured interviews to explore patients’ knowledge, attitudes and beliefs regarding ImplanonNXT®. Ten patients were interviewed at Knysna Hospital. Findings: There was confusion amongst women about the harms and benefits of using ImplanonNXT® and it became apparent contraceptive counselling during pregnancy greatly affects the choices they make. Other factors that influenced the participants’ choice with regard to contraception included social influences, preference for familiar methods and the side effect profile of the various options. Perceptions of the adverse side effects of the implantable device added to confusion and fear of this method, which influenced women’s ideas about the use of ImplanonNXT®. Poor communication and reluctance from clinic staff to discuss ImplanonNXT® during antenatal visits contributed to poor knowledge about the implantable device and its side effects. Conclusion: Clearer communication during antenatal visits with pregnant women may address some of the fears and beliefs that surround its side effects, workings and efficacy. The fear of possible side effects should be a focus for counselling and education, as it predominantly contributes to women’s confusion and fear of the device. Further research is needed to address this as well as evaluate if interventions such as better counselling and a dedicated team approach can change the attitudes and beliefs of post-partum women towards the ImplanonNXT® device in the South African district health system.